Collapsed States of Langmuir Monolayers - Phan, Minh Dinh; Lee, Jumi; Shin, Kwanwoo (Journal of Oleo Science, 2016)
Langmuir monolayers of amphiphilic molecules at an air-water interface can be compressed laterally to achieve high surface density. However, compression beyond a certain threshold causes the monolayer to become unstable, which may lead to the formation of collapsed states with topographical differences that are associated with the structures and mechanical properties of the constituent molecules of the monolayer. The mechanisms and collapsed structures can differ owing to differences in experimental conditions, i.e., temperature, ion-content, the pH of subphase, or compression rate; in addition, the type of constituent molecules, i.e., biological lipids or chemical surfactants, has an effect. In this review, we compare studies concerning several aspects of collapse, from basic concepts and theoretical mechanisms to experimental visualization of the monolayer topography. In addition, techniques often employed to study this subject are discussed in this review.